2014
DOI: 10.1523/jneurosci.0680-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cocaine Seeking Requires a Beta-2 Adrenergic Receptor-Regulated Pathway from the Ventral Bed Nucleus of the Stria Terminalis That Regulates CRF Actions in the Ventral Tegmental Area

Abstract: The ventral bed nucleus of the stria terminalis (vBNST) has been implicated in stress-induced cocaine use. Here we demonstrate that, in the vBNST, corticotropin releasing factor (CRF) is expressed in neurons that innervate the ventral tegmental area (VTA), a site where the CRF receptor antagonist antalarmin prevents the reinstatement of cocaine seeking by a stressor, intermittent footshock, following intravenous self-administration in rats. The vBNST receives dense noradrenergic innervation and expresses ␤ adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 72 publications
4
68
0
Order By: Relevance
“…All of the experiments and analyses were performed by experimenters who were blind to the treatments, and the animals’ order of treatment was randomized. No statistical methods were used to predetermine sample sizes, but our sample sizes are similar to those reported in previous publications 13,25,37,39 . Different numbers of animals between groups and between the beginning and end of the study are a result of the loss of data due to improper cannula placement, improper brain perfusion, damaged brain samples, or computer failure during testing.…”
Section: Methodsmentioning
confidence: 61%
“…All of the experiments and analyses were performed by experimenters who were blind to the treatments, and the animals’ order of treatment was randomized. No statistical methods were used to predetermine sample sizes, but our sample sizes are similar to those reported in previous publications 13,25,37,39 . Different numbers of animals between groups and between the beginning and end of the study are a result of the loss of data due to improper cannula placement, improper brain perfusion, damaged brain samples, or computer failure during testing.…”
Section: Methodsmentioning
confidence: 61%
“…Moreover, during acute opiate withdrawal, norepinephrine can act through β-receptors to increase GABA A inhibition of VTAprojecting BNST neurons (Dumont and Williams, 2004), leading to increased inhibition of the VTA. Activation of β 2 -adrenergic receptors in the vBNST drives stress-induced reinstatement by releasing CRF in the VTA (Vranjkovic et al, 2014). Although increased VTA CRF can potentiate activity (Ungless et al, 2003), CRF receptor antagonism in the VTA blocks the decrease in NAc dopamine transients caused by aversive quinine infusions (Twining et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CRF, originating from outside sources including the bed nucleus of the stria terminalis (Rodaros et al, 2007;Vranjkovic et al, 2014) or within the VTA itself (Grieder et al, 2014), acts in complex, often opposing ways and can increase or decrease excitatory and/or inhibitory transmission in the VTA through numerous mechanisms. In vitro studies have revealed that CRF 1 receptors act presynaptically on glutamatergic terminals to increase glutamatergic drive onto dopamine neurons (Williams et al, 2014), as well as exerting postsynaptic actions to increase EPSCs and firing rates of dopamine neurons (Wanat et al, 2008).…”
Section: Crf Actions In the Vta And Effort-related Decision-makingmentioning
confidence: 99%